PEMBUATAN PUPUK ORGANIK CAIR DARI LIMBAH CAIR INDUSTRI PERIKANAN MENGGUNAKAN ASAM ASETAT DAN EM4 (Effective Microorganisme 4) - YULYA FITRIA; BUSTAMI IBRAHIM; DESNIAR DESNIAR (Akuatik: Jurnal Sumberdaya Perairan, 2008)
Fishery industrial wastewater contents high in nutritional elements especially nitrogen which can be used as an organic fertilizer. In order to increase the effectivity of this wastewater as a fertilizer, the complex substances need to be brokendown become a simpler one. Acetic acid and EM4 (Effective Microorganism 4) is a chemical and biological activator which applied to degradate the complex substances. The objective of research are to study a treatment of fishery industrial wastewater to become an organic fertilizer, and to identify the quality of liquid organic fertilizer resulted when applied to spinach plant (Amaranthus tricolor). Hasil penelitian terhadap kandungan unsur hara awal limbah cair memiliki rata-rata kandungan N total, Total C organik, P tersedia dan K yang dapat dipertukarkan masing-masing adalah 628,10 mg/l; 2115,56 mg/l; 241,1 mg/l dan 246 mg/l dengan nilai pH 6,96. The observation of raw wastewater shows that N total, C organic total, available P and K ionic transfer are 628,10 mg/l; 2115,56 mg/l; 241,1 mg/l dan 246 mg/l orderly with pH value is 6,96. After treatment pH value become 5,2 - 6, 93. Content of C organic total, N total, ratio C/N, nitate, available P and K ionic transfer become 2102,83 – 9622,30 mg/l; 628,10-1064,93 mg/l; 3,69-9,04; 3,0326-4,5123 mg/l, ; 151,77-649,4 mg/l dan 157-548 mg/l orderly. When applied to spinach plant (Amaranthus tricolor) the treatment of the wastewater with activator EM4 give the best result, which has C/N ratio similar to soil, with higher in nitrogen, phosphor and kalium.